The Didactic Value of the Tari Kiamat: A Source of Cultural Literacy to Strengthen the Cultural Identity of the People of Lampung, Indonesia - Daryanti, Fitri; Sinaga, Risma Margaretha; Saputri, Amelia Hani; Taib, Muhammad Fazli (Universitas Negeri Semarang, 2025)
Traditional dance, as part of cultural heritage, not only functions as an artistic expression but also as a medium for transmitting values, knowledge, and a society’s collective memory through structured symbols. One of the main challenges in the preservation of traditional arts is the change in the mechanism of cultural inheritance, which has undergone a shift from communal and hereditary patterns to patterns that are increasingly fragmented due to modernization and social change. This condition demands a more in-depth study of how cultural values can be maintained and transformed in a relevant way for the younger generation. This study examines the dimension of didactic values in the inheritance of the Tari Kiamat, particularly in the context of traditional marriage ceremonies in Keratuan Darah Putih, a customary institution with historical significance in Lampung society. Using a qualitative descriptive method, data were collected through observation, in-depth interviews, field notes, and documentation studies, then analyzed using Miles and Huberman’s interactive analysis model. The results of the study show that the Tari Kiamat, contains didactic values such as sacredness, exclusivity, leadership, responsibility, tolerance, wisdom, and politeness. These values not only regulate social relations among indigenous peoples but also serve as ethical models for younger generations. In the context of education, didactic values should be integrated as a learning resource grounded in local wisdom to strengthen students’ cultural literacy, character, and identity.